The Determination of the citizenship of a child born on board an international aircraft: an analysis from the perspectives of international, Nigerian, and Islamic law - Mustapha, Ismail Adua (Penerbit Universiti Kebangsaan Malaysia, 2023)
Instances of childbirth occurring aboard international aircraft, while rare, pose unique legal challenges in determining the child's citizenship. Typically, pregnant women in their trimester period are not allowed to board aircraft except for medical emergencies. This article aims to conduct a comprehensive analysis of how citizenship for children born on such flights is addressed within the realms of International Law, Nigerian Law, and Islamic Law, exploring the similarities and differences in theoretical and practical applications across these legal systems. Utilizing a qualitative research methodology, this study examines both primary and secondary legal sources. The findings indicate a divergence in approaches: Under International Law, a child born on an international aircraft generally acquires the citizenship of the country where the aircraft is registered. In contrast, Nigerian and Islamic laws prioritize jus sanguinis (right of blood), where a child's citizenship is determined by the parents' nationality, superseding jus soli (right of soil) principles that confer citizenship based on the location of birth (in this case, the aircraft's nationality).